Results of 24-hour pH monitorization in laryngopharyngeal reflux cases presenting with various symptoms - Kar, Murat; San, İmran; Korkmaz, Baki; Özgönül, Abdullah; İynen, İsmail (ENT Updates, 2012)
Objective: Laryngopharyngeal reflux (LPR), an atypical form of gastroesophageal reflux (GER), may present with non-specific symptoms of upper aerodigestive system. In this study, we aimed to show the LPR frequency of various symptom groups by 24-hour double-channel pH monitorization. Methods: A total of 125 patients and 20 healthy controls were enrolled to this study between July 2007 and July 2008. Patients were assigned to 5 different groups with respect to their chief complaints (gastrointestinal, bronchial, laryngeal, pharyngeal and rhinologic). All patients underwent 24-hour double-channel pH monitorization and diagnosis of LPR was confirmed if one or more pH results were below 4.0 in proximal channel. Results: Laryngopharyngeal reflux was detected in 18 of 19 patients (94%) in gastrointestinal group, 24 of 25 patients (96%) in bronchial group, 26 of 31 patients (83%) in laryngeal group, 27 of 29 patients (93%) in pharyngeal group, 19 of 21 patients (90%) in rhinologic group and 2 of 20 patients (10%) in the control group. The highest incidence of LPR was encountered in the bronchial group, whereas the lowest incidence for LPR was detected in laryngeal group. Conclusion: Laryngopharyngeal reflux may present with a wide spectrum of symptoms in daily otorhinolaryngology practice. With respect to our results, 24-hour double-channel pH monitorization turns out to be a reliable method in the diagnosis of LPR in cases suspected for laryngopharyngeal reflux.